Hemispheric Lateralization of Auditory Working Memory Regions During Stochastic Resonance: An fMRI Study. Issue 6 (3rd December 2019) - Othman, Elza Azri; Yusoff, Ahmad Nazlim; Mohamad, Mazlyfarina; Abdul Manan, Hanani; Abd Hamid, Aini Ismafairus; Giampietro, Vincent
Abstract : Background: The auditory and prefrontal cortex supports auditory working memory processing. Many neuroimaging studies have shown hemispheric lateralization of auditory working memory brain regions in the presence of background noise, but few studies have focused on the lateralization of these regions during stochastic resonance. Purpose: To investigate the effects of stochastic resonance on lateralization of auditory working memory regions, and also to examine the brain‐behavior relationship during stochastic resonance. Study Type: Cross‐sectional. Population/Subjects: Forty healthy young adults (18–24 years old). Field Strength/Sequence: 3.0T, T1, and T2 *‐weighted imaging. Assessment: The auditory working memory performance was assessed using a backward recall task. Functional magnetic resonance imaging (fMRI) was used to measure brain activity during task performance. Functional MRI data were analyzed using SPM12 and WFU PickAtlas. Statistical Tests: One‐way independent analyses of variance (ANOVA) were conducted on the behavioral and functional data to examine the main effect of noise level on performance ( P  < 0.01) and brain activity ( P  < 0.0042). Hemispheric lateralization was determined by calculating the laterality index. A paired samples t ‐test was performed to compare brain activity between hemispheres ( P  < 0.05). Pearson's correlation analysis and simple linear regression ( P  < 0.0042) were used to examine the relationship between brain activity and behavioral performance. Results: Performance was significantly enhanced during the 50 and 55 dB sound pressure level (SPL) conditions via the stochastic resonance mechanism [ F (1, 195) = 49.17, P  < 0.001]. Activity of the right superior frontal gyrus in the 55 dB SPL condition was significantly positively correlated with performance (R 2 = 0.681, P  < 0.001). Data Conclusion: Our findings demonstrate changes in the lateralization of auditory working memory regions during stochastic resonance and suggest that the right superior frontal gyrus may be a strategic structure involved in the enhancement of auditory working memory performance. Level of Evidence: 2 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2020;51:1821–1828.